The CO2 fertilization effect on leaf photosynthesis of maize (Zea mays L.) depends on growth temperatures with changes in leaf anatomy and soluble sugars - Liu, Liang; Hao, Lihua; Zhang, Yunxin; Zhou, Haoran; Ma, Baoguo; Cheng, Yao; Tian, Yinshuai; Chang, Zhijie; Zheng, Yunpu (Frontiers in Plant Science, 2022)
Understanding the potential mechanisms and processes of leaf photosynthesis in response to elevated CO2 concentration ([CO2]) and temperature is critical to estimating the impacts of climatic change on the growth and yield in crops such as maize (Zea mays L.), which is a widely cultivated C4 crop all over the world. We examined the combined effect of elevated [CO2] and temperature on plant growth, leaf photosynthesis, stomatal traits, and biochemical compositions of maize with six environmental growth chambers controlling two CO2 levels (400 µmol mol-1 and 800 µmol mol-1) and three temperature regimes (25/19°C, 31/25°C, and 37/31°C). We found that leaf photosynthesis was significantly enhanced by increasing growth temperature from 25/19°C to 31/25°C independent of [CO2]. However, leaf photosynthesis dramatically declined when the growth temperature was continually increased to 37/31°C at both ambient CO2 concentration (400 µmol mol-1, a[CO2]) and elevated CO2 concentration (800 µmol mol-1, e[CO2]). Meanwhile, we also found strong CO2 fertilization effct on maize plants grown at the highest temperature (37/31°C), as evidenced by the higher leaf photosynthesis at e[CO2] than that at a[CO2], although leaf photosynthesis was similar between a[CO2] and e[CO2] under the other two temperature regimes of 25/19°C and 31/25°C. Furthermore, we also found that e[CO2] resulted in the increase of leaf soluble sugar, which was positively related with leaf photosynthesis under the high temperature regime of 37/31°C (R2 = 0.77). In addition, our results showed that e[CO2] substantially decreased leaf transpiration rates of maize plants, which might be partially attributed to the reduced stomatal openness as evidenced by the decreased stomatal width and stomatal area. These results suggest that the CO2 fertilization effect on plant growth and leaf photosynthesis of maize depends on growth temperatures through changing stomatal traits, leaf anatomy, and soluble sugar contents.